2014
DOI: 10.1371/journal.pone.0095186
|View full text |Cite
|
Sign up to set email alerts
|

The Melanogenesis Alteration Effects of Achillea millefolium L. Essential Oil and Linalyl Acetate: Involvement of Oxidative Stress and the JNK and ERK Signaling Pathways in Melanoma Cells

Abstract: The mitogen-activated protein kinase (MAPK) family, including extracellular signal-regulated kinase (ERK)1/2, c-Jun N-terminal kinase (JNK)1/2 and p38 MAPK, is known to be activated by ultraviolet (UV) radiation in melanocytes to regulate melanin production. Reactive oxygen species (ROS) play important roles in the pathway of ERK and JNK activation. It has been established that the essential oil of Achillea millefolium L. (AM-EO) has activities that suppress the oxidative stress and inflammatory responses. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 28 publications
(31 reference statements)
2
58
0
Order By: Relevance
“…The major compound of Salvia sclarea EO (sample 5) was linalyl acetate (45.1%), which was recently demonstrated to account for the anti‐melanogenic action of Achillea millefolium EO, by downregulating tyrosinase activity in α‐MSH‐stimulated B16 cells . However, in our study, EO 5 resulted in a weak mushroom tyrosinase inhibitor, thus suggesting that linalyl acetate may not directly inhibit the enzymatic action and that its anti‐melanogenic effect depended mainly on its ability to interfere with the signalling pathways that trigger tyrosinase gene expression, as also suggested by Peng et al …”
Section: Resultsmentioning
confidence: 52%
“…The major compound of Salvia sclarea EO (sample 5) was linalyl acetate (45.1%), which was recently demonstrated to account for the anti‐melanogenic action of Achillea millefolium EO, by downregulating tyrosinase activity in α‐MSH‐stimulated B16 cells . However, in our study, EO 5 resulted in a weak mushroom tyrosinase inhibitor, thus suggesting that linalyl acetate may not directly inhibit the enzymatic action and that its anti‐melanogenic effect depended mainly on its ability to interfere with the signalling pathways that trigger tyrosinase gene expression, as also suggested by Peng et al …”
Section: Resultsmentioning
confidence: 52%
“…In the presence of UV irradiation, activation of JNK serves as a key kinase in fibroblasts and keratinocytes . It was reported that the JNK pathway participates in regulating melanogenesis . Han et al indicated that JNK activation is highly related to TRP1 protein expression and melanin expression in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cogn .) downregulated the expression levels of p38, CREB, MITF, TYR, TRP1, and TRP2 in a dose‐dependent manner . It was suggested that Achillea millefolium L. EO suppressed melanin production in B16 cell line via reduction of the phosphorylated‐JNK while enhancing the phosphorylated‐ERK without affecting the phosphorylated‐p38 MAPK …”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%